Challenges of Using Multimedia Tools in the Teaching and Learning Process: Instance from a college of Bangladesh (Journal of Management and Business Education, 2024)
The growing acceptance of multimedia-based education among students and its effectiveness are the reasons behind its popularity. Multimedia instruction in the classroom presents several challenges in addition to opportunities. Thus, the study aims to highlight the difficulties of using multimedia resources in the classroom and explore potential solutions. To evaluate the efficacy of multimedia technologies in the current teaching-learning process, the first focus of this study was on how to get data from the teachers and students of Patuakhali Government College (PGC). Second, a questionnaire was used to guide the conduct of six case studies and two focus group discussions (FGDs). In this study, the qualitative research method was employed. It is significant to note that, according to the opinions and data gathered for this study, most educators and students concur that teachers have no interest in implementing multimedia resources in the classroom. Factors such as slow internet connectivity, lack of adequate teacher training, inadequate digital classrooms and inconsistency in teacher-student ratio were identified in the study’s findings. The results of case studies and focus group discussions (FGD) helped to identify the difficulties associated with employing multimedia tools in the classroom. Addressing all these challenges can effectively ensure an up-to-date education system in tune with the global educational landscape.
Keywords: Multimedia instruments; Information and Communication Technology; ICT; skill development; digital content; Teacher’s reluctance; Information; communication; skill